(untitled) (Journal of Association of Educational Management and Policy Practitioners, 2024)
This study investigated institutional variables predictors of secondary school teachers job effectiveness. One research question and one null hypothesis was tested. Descriptive survey research design was adopted. The population of the study comprises of 2053 teachers, a sample of 288 teachers were adopted for the study. The instrument tagged institutional variable predictors of secondary schools teacher job effectiveness was used for data collection (Questionnaire IVP SSTJEEQ) designed by the researcher, validated by two experts in test and measurement and educational management. To determine the reliability of the instrument, Cronbach Alpha reliability test was applied from 0.71 – 0.84. Data was analyzed using simple regression analysis and the result showed that institutional variables such as school facility predict teachers job effectiveness in the study area. It was concluded that school facility predict or influence teachers job effectiveness. It was recommended among other that government should provide school facility to enhance high level productivity of the teachers.